Individual increase in inbreeding allows estimating effective sizes from pedigrees - Gutiérrez, Juan Pablo (BioMed Central, 2008)
We present here a simple approach to obtain reliable estimates of the effective population size in real world populations via the computation of the increase in inbreeding for each individual (delta F(i)) in a given population. The values of delta F(i )are computed as t-root of 1 - (1 - F(i)) where F(i )is the inbreeding coefficient and t is the equivalent complete generations for each individual. The values of delta F computed for a pre-defined reference subset can be averaged and used to estimate effective size. A standard error of this estimate of N(e )can be further computed from the standard deviation of the individual increase in inbreeding. The methodology is demonstrated by applying it to several simulated examples and to a real pedigree in which other methodologies fail when considering reference subpopulations. The main characteristics of the approach and its possible use are discussed both for predictive purposes and for analyzing genealogies.